2014
DOI: 10.1002/ajoc.201402052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Tetrahydropyran Fragment of Bistramide D

Abstract: A synthesis of the tetrahydropyran (THP) moiety of bistramide D has been completed by using cross‐metathesis and kinetically controlled intramolecular oxa‐Michael addition to form the ring with excellent trans selectivity. The C9 methyl substituent was introduced by using an unsaturated sulfone building block, which can be most effectively prepared through a combination of diastereoselective allylation and alkene isomerisation. The effect of this methyl group on subsequent cross‐metathesis reactions can be mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Chemical IMOMA, often integrated into efficient tandem processes, gained growing attention for the stereoselective synthesis of tetrahydropyrans (THPs) during recent years. It has been shown that the cis - or trans -THP selectivity of IMOMA can be influenced by kinetic or thermodynamic reaction control, by the type of activation (acid, base, or metal catalysis), by the configuration of the double bond, and by the nature of the acceptor moiety. Although the reaction outcome is predictable for some systems (tandem-cross metathesis-IMOMA with vinylketone intermediates for example reliably leads to cis -THPs with diastereomeric excess > 5:1), low to moderate d.e. s are rather common and have only occasionally been improved by extensive reaction optimization or product re-equilibration (see, e.g., refs ). Pioneering studies on the thioester IMOMA have provided valuable insight into the reasons for the high substrate dependence of the cis - trans selectivity, along with the establishment of guidelines for diastereoselective THP cyclization in specific systems. …”
Section: Introductionmentioning
confidence: 99%
“…Chemical IMOMA, often integrated into efficient tandem processes, gained growing attention for the stereoselective synthesis of tetrahydropyrans (THPs) during recent years. It has been shown that the cis - or trans -THP selectivity of IMOMA can be influenced by kinetic or thermodynamic reaction control, by the type of activation (acid, base, or metal catalysis), by the configuration of the double bond, and by the nature of the acceptor moiety. Although the reaction outcome is predictable for some systems (tandem-cross metathesis-IMOMA with vinylketone intermediates for example reliably leads to cis -THPs with diastereomeric excess > 5:1), low to moderate d.e. s are rather common and have only occasionally been improved by extensive reaction optimization or product re-equilibration (see, e.g., refs ). Pioneering studies on the thioester IMOMA have provided valuable insight into the reasons for the high substrate dependence of the cis - trans selectivity, along with the establishment of guidelines for diastereoselective THP cyclization in specific systems. …”
Section: Introductionmentioning
confidence: 99%
“…for preparation of a bistramide A segment [446], with allylic alcohols (followed by oxidation) for the preparation of γ-keto-α,β-unsaturated esters [447], with an alkene-dihydropyridone for preparation of the dihydrolycolucine skeleton [448], with vinyldioxolane derivatives [449], with alkenes connected to cellulose derivatives [450]; with fatty-acid derived alkene-carbamates for preparation of renewable polyesters and polyamides [451], with a passerine-derived triene for eventual dendrimer preparation (three-fold CM) [452],…”
Section: )mentioning
confidence: 99%
“…We have previously shown that diene 4 can undergo crossmetathesis with methyl acrylate efficientlyu sing the HoveydaGrubbs II catalyst. [10] Attempts to achieve ac ross-metathesis reaction with the homoallylic mesylate 15, [25] which would provide the remaining carbon atoms and stereogenic centre,r esulted, however,i no nly at race of the desired product, accompanied by both possible pseudodimers (Scheme 4). Both metathesis partners suffer from sterich indrance due to allylic substituents.…”
mentioning
confidence: 99%